A new benchmark of soft X-ray transition energies of Ne , CO 2 , and SF 6 : paving a pathway towards ppm accuracy - Stierhof, Jakob; Kühn, S.; Winter, Mirko; Micke, P.; Steinbrügge, R.; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (European Physical Journal D, 2022)
Abstract: A key requirement for the correct interpretation of high-resolution X-ray spectra is that transition energies are known with high accuracy and precision. We investigate the K-shell features of Ne , CO 2, and SF 6 gases, by measuring their photo ion-yield spectra at the BESSY II synchrotron facility simultaneously with the 1s–np fluorescence emission of He-like ions produced in the Polar-X EBIT. Accurate ab initio calculations of transitions in these ions provide the basis of the calibration. While the CO 2 result agrees well with previous measurements, the SF 6 spectrum appears shifted by ∼ 0.5 eV, about twice the uncertainty of the earlier results. Our result for Ne shows a large departure from earlier results, but may suffer from larger systematic effects than our other measurements. The molecular spectra agree well with our results of time-dependent density functional theory. We find that the statistical uncertainty allows calibrations in the desired range of 1–10 meV, however, systematic contributions still limit the uncertainty to ∼ 40–100 meV, mainly due to the temporal stability of the monochromator energy scale. Combining our absolute calibration technique with a relative energy calibration technique such as photoelectron energy spectroscopy will be necessary to realize its full potential of achieving uncertainties as low as 1–10 meV. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-03-11

An in-depth analysis of the variable cyclotron lines in GX 301-2 - Zalot, Nicolas; Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Ballhausen, Ralf; Zainab, Aafia; Pottschmidt, Katja; Fürst, Felix; Thalhammer, Philipp; Islam, Nazma; Diez, Camille M.; Kretschmar, Peter; Berger, Katrin; et al. (Astronomy & Astrophysics, 2024)
Context. The high-mass X-ray binary system GX 301-2 is a persistent source with a well-known variable cyclotron line centered at 35 keV. Recently, a second cyclotron line at 50 keV has been reported with a presumably different behavior than the 35 keV line. Aims. We investigate the presence of the newly discovered cyclotron line in the phase-averaged and phase-resolved spectra at higher luminosities than before. We further aim to determine the pulse-phase variability of both lines. Methods. We analyze a NuSTAR observation of GX 301-2 covering the pre-periastron flare, where the source luminosity reached its peak of ∼4× 1037 erga s-1 in the 5 -50 keV range. We analyze the phase-averaged spectra in the NuSTAR energy range from 3.5- 79 keV for both the complete observation and three time segments of it. We further analyze the phase-resolved spectra and the pulse-phase variability of continuum and cyclotron line parameters. Results. We confirm that the description of the phase-averaged spectrum requires a second absorption feature at 51.5-1.0+1.1 keV besides the established line at 35 keV. The statistical significance of this feature in the phase-averaged spectrum is > 99.999%. We further find that the 50 keV cyclotron line is present in three out of the eight phase bins. Conclusions. Based on the results of our analysis, we confirm that the detected absorption feature is very likely to be a cyclotron line. We discuss a variety of physical scenarios that could explain the proposed anharmonicity, but also outline circumstances under which the lines are harmonically related. We further present the cyclotron line history of GX 301-2 and evaluate concordance among each other. We also discuss an alternative spectral model including cyclotron line emission wings.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Stars: magnetic field; Stars: neutron; X-rays: binaries

Correction to: A new benchmark of soft X-ray transition energies of Ne, CO2, and SF6: paving a pathway towards ppm accuracy (The European Physical Journal D, (2022), 76, 3, (38), 10.1140/epjd/s10053-022-00355-0) - Stierhof, Jakob; Kuehn, S.; Winter, Michael; Micke, Peter; Steinbruegge, R.; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (European Physical Journal D, 2022)
CRIS-Team Scopus Importer:2022-11-11

Fitting strategies of accretion column models and application to the broadband spectrum of Cen X-3 - Thalhammer, Philipp; Bissinger, Matthias; Ballhausen, Ralf; Pottschmidt, Katja; Wolff, Michael T.; Stierhof, Jakob; Sokolova-Lapa, Ekaterina; Furst, Felix; Malacaria, Christian; Gottlieb, Amy; Marcu-Cheatham, Diana M.; Becker, Peter A.; et al. (Astronomy & Astrophysics, 2021)
Due to the complexity of modeling the radiative transfer inside the accretion columns of neutron star binaries, their X-ray spectra are still commonly described with phenomenological models, for example, a cutoff power law. While the behavior of these models is well understood and they allow for a comparison of different sources and studying source behavior, the extent to which the underlying physics can be derived from the model parameters is very limited. During recent years, several physically motivated spectral models have been developed to overcome these limitations. Their application, however, is generally computationally much more expensive and they require a high number of parameters which are difficult to constrain. Previous works have presented an analytical solution to the radiative transfer equation inside the accretion column assuming a velocity profile that is linear in the optical depth. An implementation of this solution that is both fast and accurate enough to be fitted to observed spectra is available as a model in XSPEC. The main difficulty of this implementation is that some solutions violate energy conservation and therefore have to be rejected by the user. We propose a novel fitting strategy that ensures energy conservation during the chi(2)-minimization which simplifies the application of the model considerably. We demonstrate this approach as well as a study of possible parameter degeneracies with a comprehensive Markov-chain Monte Carlo analysis of the complete parameter space for a combined NuSTAR and Swift/XRT dataset of Cen X-3. The derived accretion-flow structure features a small column radius of similar to 63 m and a spectrum dominated by bulk-Comptonization of bremsstrahlung seed photons, in agreement with previous studies.
CRIS-Team WoS Importer:2021-12-17

High-Precision Determination of Oxygen Kα Transition Energy Excludes Incongruent Motion of Interstellar Oxygen - Leutenegger, M. A.; Kühn, S.; Micke, P.; Steinbrügge, R.; Stierhof, Jakob; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (Physical Review Letters, 2020)
We demonstrate a widely applicable technique to absolutely calibrate the energy scale of x-ray spectra with experimentally well-known and accurately calculable transitions of highly charged ions, allowing us to measure the K-shell Rydberg spectrum of molecular O2 with 8 meV uncertainty. We reveal a systematic ∼450 meV shift from previous literature values, and settle an extraordinary discrepancy between astrophysical and laboratory measurements of neutral atomic oxygen, the latter being calibrated against the aforementioned O2 literature values. Because of the widespread use of such, now deprecated, references, our method impacts on many branches of x-ray absorption spectroscopy. Moreover, it potentially reduces absolute uncertainties there to below the meV level.
CRIS-Team Scopus Importer:2020-12-25

High Resolution Photoexcitation Measurements Exacerbate the Long-Standing Fe XVII Oscillator Strength Problem - Kuehn, Steffen; Shah, Chintan; Lopez-Urrutia, Jose R. Crespo; Fujii, Keisuke; Steinbruegge, Rene; Stierhof, Jakob; Togawa, Moto; Harman, Zoltan; Oreshkina, Natalia S.; Cheung, Charles; Kozlov, Mikhail G.; Porsev, Sergey G.; et al. (Physical Review Letters, 2020)
For more than 40 years, most astrophysical observations and laboratory studies of two key soft x-ray diagnostic 2p-3d transitions, 3C and 3D, in Fe XVII ions found oscillator strength ratios f(3C)/f(3D) disagreeing with theory, but uncertainties had precluded definitive statements on this much studied conundrum. Here, we resonantly excite these lines using synchrotron radiation at PETRA III, and reach, at a millionfold lower photon intensities, a 10 times higher spectral resolution, and 3 times smaller uncertainty than earlier work. Our final result of f(3C)/f(3D)=3.09(8)(6) supports many of the earlier clean astrophysical and laboratory observations, while departing by five sigmas from our own newest large-scale ab initio calculations, and excluding all proposed explanations, including those invoking nonlinear effects and population transfers.
CRIS-Team Scopus Importer:2021-04-19

Observation of strong two-electron-one-photon transitions in few-electron ions - Togawa, Moto; Kuehn, S.; Shah, Chintan; Amaro, Pedro; Steinbruegge, R.; Stierhof, Jakob; Hell, N.; Rosner, M.; Fujii, Keisuke; Bissinger, Matthias; Ballhausen, Ralf; Hoesch, M.; et al. (Physical Review A, 2020)
We resonantly excite the K series of O5+ and O6+ up to principal quantum number n=11 with monochromatic x rays, producing K-shell holes, and observe their relaxation by soft-x-ray emission. Some photoabsorption resonances of O5+ reveal strong two-electron-one-photon (TEOP) transitions. We find that for the [(1s2s)15p3/2]3/2;1/2 states, TEOP relaxation is by far stronger than the radiative decay and competes with the usually much faster Auger decay path. This enhanced TEOP decay arises from a strong correlation with the near-degenerate upper states [(1s2p3/2)14s]3/2;1/2 of a Li-like satellite blend of the He-like Kα transition. Even in three-electron systems, TEOP transitions can play a dominant role, and the present results should guide further research on the ubiquitous and abundant many-electron ions where electronic energy degeneracies are far more common and configuration mixing is stronger.
CRIS-Team Scopus Importer:2021-04-19

The giant outburst of EXO 2030+375: I. Spectral and pulse profile evolution - Thalhammer, Philipp; Ballhausen, R.; Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Zainab, Aafia; Staubert, R.; Pottschmidt, K.; Coley, Joel B.; Rothschild, R. E.; Jaisawal, G. K.; West, B.; Becker, P. A.; et al. (Astronomy & Astrophysics, 2024)
The Be X-ray binary EXO 2030+375 went through its third recorded giant outburst from June 2021 to early 2022. We present the results of both spectral and timing analysis based on NICER monitoring, covering the 2-10 keV flux range from 20 to 310 mCrab. Dense monitoring with observations carried out about every second day and a total exposure time of 160 ks allowed us to closely track the source evolution over the outburst. Changes in the spectral shape and pulse profiles showed a stable luminosity dependence during the rise and decline. The same type of dependence has been seen in past outbursts. The pulse profile is characterized by several distinct peaks and dips. The profiles show a clear dependence on luminosity with a stark transition at a luminosity of 2 × 1036 erg s-1, indicating a change in the emission pattern. Using relativistic raytracing, we demonstrate how anisotropic beaming of emission from an accretion channel with a constant geometrical configuration can give rise to the observed pulse profiles over a range of luminosities.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Stars: neutron; X-rays: binaries; X-rays: individuals: EXO 2030+375

Vacuum polarization alters the spectra of accreting X-ray pulsars - Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Dauser, Thomas; Wilms, Jörn (Astronomy & Astrophysics, 2023)
It is a common belief that for magnetic fields typical of accreting neutron stars in high-mass X-ray binaries vacuum polarization only affects the propagation of polarized emission in the neutron star magnetosphere. We show that vacuum resonances can significantly alter the emission from the poles of accreting neutron stars. The effect is similar to vacuum polarization in the atmospheres of isolated neutron stars and can result in suppression of the continuum and the cyclotron lines. It is enhanced by magnetic Comptonization in the hot plasma and proximity to the electron cyclotron resonance. We present several models to illustrate the vacuum polarization effect for various optically thick media and discuss how the choice of polarization modes affects the properties of the emergent radiation by simulating polarized energy- and angle-dependent radiative transfer. Polarization effects, including vacuum polarization, crucially alter the emission properties. Together with strongly angle- and energy-dependent magnetic Comptonization, they result in a complex spectral shape, which can be described by dips and humps on top of a power-law-like continuum with high-energy cutoff. These effects provide a possible explanation for the common necessity of additional broad Gaussian components and two-component Comptonization models that are used to describe spectra of accreting X-ray pulsars. We also demonstrate the character of depolarization introduced by the radiation fielda's propagation inside the inhomogeneous emission region.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Magnetic fields; Methods: numerical; Polarization; Radiative transfer; Stars: neutron; X-rays: binaries